1993
DOI: 10.1073/pnas.90.21.10305
|View full text |Cite
|
Sign up to set email alerts
|

Increasing cAMP attenuates activation of mitogen-activated protein kinase.

Abstract: Activation of the mitogen-activated protein kinase (MAP kinase) isoforms ERK1 and ERK2 was investigated in rat adipocytes. Kinase activities were measured by using myelin basic protein as substrate after the isoforms were resolved by Mono Q chromatography or by immunoprecipitation with specific antibodies. Insulin increased the activity of both isoforms by 3-to 4-fold. The 3-adrenergic agonist isoproterenol was without effect in the absence of insulin but markedly reduced the increases in ERK1 and ERK2 activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
240
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(262 citation statements)
references
References 45 publications
21
240
1
Order By: Relevance
“…Therefore, tumors that express two or more of these growth factors may require a cocktail of anticancer drugs. In contrast, b2AR stimulation will block activation of the Raf-1/Mek-1/Erk1/2 pathway when it is driven by several growth factors as they all require Mek to activate Erk1/2 (Graves et al, 1993;Sevetson et al, 1993;Wu et al, 1993;Sebolt-Leopold, 2000;Dumaz and Marais, 2005). For example, we have shown that growth factor (i.e., EGF) stimulation of P-Erk1/2 is blocked by ARA-211 in MDA-MB-231 cells (data not shown).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Therefore, tumors that express two or more of these growth factors may require a cocktail of anticancer drugs. In contrast, b2AR stimulation will block activation of the Raf-1/Mek-1/Erk1/2 pathway when it is driven by several growth factors as they all require Mek to activate Erk1/2 (Graves et al, 1993;Sevetson et al, 1993;Wu et al, 1993;Sebolt-Leopold, 2000;Dumaz and Marais, 2005). For example, we have shown that growth factor (i.e., EGF) stimulation of P-Erk1/2 is blocked by ARA-211 in MDA-MB-231 cells (data not shown).…”
Section: Discussionmentioning
confidence: 81%
“…In normal cells, it has been shown that adrenergic stimulation can either stimulate or inhibit P-Erk1/2 and proliferation (Sevetson et al, 1993;Maudsley et al, 2000;Stork and Schmitt, 2002). However, in tumor cells, it is not known if stimulation of the b2AR can stimulate tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cAMP also inhibits insulin and growth-factor-stimulated MAPK signalling in most cell types [25,[37][38][39][40], with the exception of Swiss 3T3 and PC12 cells (reviewed in [25]). Our previous studies have shown that SpcAMP counter-regulates insulin's effect on PP-2A inactivation by decreasing the tyrosine phosphorylation of PP-2A and restoring its catalytic activity [25].…”
Section: Discussionmentioning
confidence: 99%
“…We indeed found that NT increased cAMP levels in CHO-hNTR cells (results not shown). Because hydrolysis-resistant cAMP analogues such as dibutyryl cAMP or 8-Br-cAMP, which maintain high cellular levels of cAMP, are able either to prevent or to increase the MAPK level, depending on the cell type [34], we examined whether MAPK activation could be related to cAMP metabolism. In CHO-hNTR cells, cAMP analogues alone did not significantly affect this activity.…”
Section: Transduction Pathway Between Ntr and Mapksmentioning
confidence: 99%